PERAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA TANGERANG SELATAN DALAM PENGAWASAN INFRASTRUKTUR DRAINASE TAHUN 2023: The Role Of The Regional People’s Representative Council Of South Tangerang City In Monitoring Drainage Infrastructure In 2023 - Rania Dhiyarasy Shantini; Reni Dwi Purnomowati (Faculty of Law, Universitas Trisakti, 2025)
DPRD is the representation of the local people who function as part of the local government. One of the functions of the DPRD is the supervisory function. There are problems in drainage infrastructure in South Tangerang such as the lack of adequate water infiltration in some areas that cause flooding, and differences in drainage budgets in 2023, then the question arises how the role of DPRD supervision of drainage infrastructure based on Law Number 23 of 2014 concerning Regional Government, and how DPRD constraints on the supervision of drainage infrastructure 2023. This research applies socio-legal method with interview method. The results and conclusions of this study are the supervisory role of the South Tangerang DPRD, namely indirect supervision such as commission IV working meetings, the drainage budget until the third quarter only reached 58.25%, which shows that the DPRD's supervision of the 2023 drainage program is less than optimal based on Article 149 paragraph 1 letter b of Law 23 of 2014 concerning Regional Government. As well as obstacles to the supervision of the South Tangerang City DPRD, namely, the lack of knowledge of DPRD members' supervision of the infrastructure development process, and ideological differences between DPRD members.